Newborn with classical Cornelia de Lange syndrome: A rare case report - Sopori, Ayush; Bajaj, Mohit; Sharma, Jyoti; Jangwal, Chetna (Indian Journal of Case Reports, 2020)
Cornelia de Lange syndrome (CdLS) is a rare multisystem developmental disorder associated with multiple congenital malformations including facial dysmorphism, upper-extremity malformations, hirsutism, cardiac defects, gastrointestinal abnormalities, and central nervous system anomalies. In the neonatal period, typical facial features help in diagnosing it. Here, we report a neonate with facial features (bushy eyebrows, synophrys, long eyelashes, micrognathia, hirsutism, and low hairline), gastroesophageal reflux disease, large atrial septal defect, and neonatal seizures diagnosed as classic CdLS.